Co-design of a Virtual Reality Cognitive Remediation Program for Depression (bWell-D) With Patient End Users and Clinicians: Qualitative Interview Study Among Patients and Clinicians - Maria Elena Hernandez Hernandez; Erin Michalak; Nusrat Choudhury; Mark Hewko; Ivan Torres; Mahesh Menon; Raymond W Lam; Trisha Chakrabarty (JMIR Publications, 2023)
BackgroundMajor depressive disorder (MDD) is the leading cause of global disability; however, the existing treatments do not always address cognitive dysfunction-a core feature of MDD. Immersive virtual reality (VR) has emerged as a promising modality to enhance the real-world effectiveness of cognitive remediation. ObjectiveThis study aimed to develop the first prototype VR cognitive remediation program for MDD ("bWell-D"). This study gathered qualitative data from end users early in the design process to enhance its efficacy and feasibility in clinical settings. MethodsSemistructured end-user interviews were conducted remotely (n=15 patients and n=12 clinicians), assessing the participants' perceptions and goals for a VR cognitive remediation program. Video samples of bWell-D were also shared to obtain feedback regarding the program. The interviews were transcribed, coded, and analyzed via thematic analysis. ResultsEnd users showed an optimistic outlook toward VR as a treatment modality, and perceived it as a novel approach with the potential of having multiple applications. The participants expressed a need for an engaging VR treatment that included realistic and multisensorial settings and activities, as well as customizable features. Some skepticism regarding its effectiveness was also reported, especially when the real-world applications of the practiced skills were not made explicit, as well as some concerns regarding equipment accessibility. A home-based or hybrid (ie, home and clinic) treatment modality was preferred. ConclusionsPatients and clinicians considered bWell-D interesting, acceptable, and potentially feasible, and provided suggestions to enhance its real-world applicability. The inclusion of end-user feedback is encouraged when developing future VR programs for clinical purposes.